ANALISIS PERENCANAAN DAN PENGANGGARAN PROGRAM KESISWAAN BERDASARKAN MISI DI SMK NEGERI 1 PERCUT SEI TUAN - Ramadhani, Gita; Daryanto, Eka; Restu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the planning and budgeting process for student programs at SMK Negeri 1 Percut Sei Tuan. This research is descriptive qualitative research. The data collection technique used is interviews with related parties such as school principals, deputy principals, teachers and students as well as collecting documentation such as School Work Plans and Budgets (RKAS). The results show that ongoing student programs are planned with adjustments to the mission. The activities are in the form of TOEIC, PKL, MBS and extracurricular tests and simulations which are able to improve students' skills in accordance with the stated mission. In the budget aspect, obstacles were found such as limited funds and bureaucratic complexity. Schools address this by prioritizing budgets and improving coordination and dedicated management teams so that obstacles can be overcome.